The Impact of Creativity on Primary, Secondary, and University Education in a Knowledge-Based Society - Lai, Yitong (Transactions on Social Science, Education and Humanities Research, 2024)
Due to the unfolding of the third technological revolution and the development of a knowledge-based society, there is an increasing demand for knowledge, particularly driven by the need for innovation. This has elevated the requirement for creativity, which, for the foundation of society, is reflected in education. The theme of this paper is the manifestation of creativity, innovative ability, and innovative thinking in the field of education, along with recommendations for promoting their development. Through literature research, the author aims to understand the impact of creativity on education at different stages and address the lack of creativity among young people by suggesting improvements to the educational model. After some kind of research, the result is that creativity will have different influences among ages. In primary school, teachers should pay more attention to their imagination; in terms of secondary school, teachers need to focus on students’ hands-on ability; as for the college students, teachers ought to encourage them to innovate. So, in order to advance their creative ability to prepare a knowledge-based society in the future, the author also gives some scientific suggestions.